Bioactivity of Solanum melongena L. and Capsicum annuum L. on Callosobruchus maculatus (Coleoptera: Bruchidae) (2016)
The continuous and indiscriminate use of chemicals in agriculture can bring serious problems to human health and the environment. One option is the use of plants with insecticidal action. Given the above, the aim of this work was to evaluate the insecticide activity powder of leaves of Solanum melongena L. and Capsicum annuum L. against Callosobruchus maculatus in three concentrations. The experiment was conducted at the Laboratory of Entomology, Federal University of Campina Grande (UFCG), Campus de Pombal, Paraiba, Brazil. The grains of cowpea were treated with the powders in concentrations 0.0, 2.5, 5.0 and 10.0 % [100*(mass of powder/ mass of grains)] and performed tests of survival and repellency against C. maculatus. Survival data were analyzed using the Log-rank test (p ≤ 0.05) by D-collet method and the repellence we used the Chi-square test (p ≤ 0.05). All post and concentrations were repellent C. maculatus except the C. annuum powder at a concentration of 2.5 % that was not statistically significant difference. With respect to survival, both plant species caused high mortality on C. maculatus, with total kill insects up to 120 h.